Dual-drug delivery of Ag-chitosan nanoparticles and phenytoin via core-shell PVA/PCL electrospun nanofibers - ŞAHİN, ALİ; RAYAMAN, ERKAN; ÇAM, MUHAMMET EMİN; GÜNDÜZ, OĞUZHAN (ELSEVIER SCI LTD, 2021)
Dual-drug delivery systems were constructed through coaxial techniques, which were convenient for the model drugs used the present work. This study aimed to fabricate core-shell electrospun nanofibrous membranes displaying simultaneous cell proliferation and antibacterial activity. For that purpose, phenytoin (Ph), a well-known proliferative agent, was loaded into a polycaprolactone (PCL) shell membrane, and as-prepared silver-chitosan nanoparticles (Ag-CS NPs), as biocidal agents, were embedded in a polyvinyl alcohol (PVA) core layer. The morphology, chemical composition, mechanical and thermal properties of the nanofibrous membranes were characterized by FESEM/STEM, FTIR and DSC. The coaxial PVA-Ag CS NPs/PCL-Ph nanofibers (NFs) showed more controlled Ph release than PVA/PCL-Ph NFs. There was notable improvement in the morphology, thermal, mechanical, antibacterial properties and cytobiocompatibility of the fibers upon incorporation of Ph and Ag-CS NPs. The proposed core-shell PVA/PCL NFs represent promising scaffolds for tissue regeneration and wound healing by the effective dual delivery of phenytoin and Ag-CS NPs.
Keywords: Silver nanoparticles; Chitosan; Phenytoin; Dual-drug delivery; Core-shell nanofibers; SILVER NANOPARTICLES; WOUND DRESSINGS; CONTROLLED-RELEASE; COMPOSITE; FABRICATION; ALGINATE; FIBERS